2010
DOI: 10.1021/jm901866m
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ferrocenic Steroidal Drug Derivatives and Their Bioactivities

Abstract: Seven novel ferrocenic derivatives, compounds 1-7, were synthesized from steroidal drugs by Aldol condensation reaction. The derivatives were purified by chromatography, and their structures were determined on the basis of HR-ESI-MS and two-dimensional NMR spectroscopy. The purity of all derivatives was more than 95%. Compounds 1-5 demonstrated anti-proliferative activity on HeLa cell line by SRB assay more than their parent compounds. All seven derivatives showed anti-oxidative activities evaluated by DPPH sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…All the determinations were performed in triplicate. The SC 50 was determined as the sample concentration that resulted in a 50% reduction of total free radical (Manosroi et al, 2008;Wu & Wang, 2008).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…All the determinations were performed in triplicate. The SC 50 was determined as the sample concentration that resulted in a 50% reduction of total free radical (Manosroi et al, 2008;Wu & Wang, 2008).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Androgens (e.g., testosterone) are sex hormones that are required for normal growth and functional activities of the human prostate. These hormones are able to interact with the androgen receptors and form a stable receptor-ligand complex [14][15][16]. Several organometallic steroidal complexes containing ferrocenyl were synthesized by Top et al and the reported antiproliferative effect of these compounds on the hormone-independent prostate cancer cells PC-3 is stronger compared to the ferrocenyl derivative of the nonsteroidal antiandrogen nilutamide [17].…”
Section: Introductionmentioning
confidence: 99%
“…Mansroi and coworkers published a series ferrocenyl vectorized with steroidal derivatives of estrogens and androgens, Chart 6 [51]. …”
Section: Target Specific Drugs For Breast and Prostate Cancersmentioning
confidence: 99%
“…These ferrocenic steroidal compounds ( 10–14 ) were screened in human cervical adenocarcinoma cell line (HeLa) and compared to doxorubicin, Table 6 [51]. Ferrocenic testosterone and methyl testosterone derivatives 10 and 11 showed GI 50 (50% cell growth inhibition) values corresponding that of doxorubicin, 0.223, 0.271 and 0.250 μg/mL respectively.…”
Section: Target Specific Drugs For Breast and Prostate Cancersmentioning
confidence: 99%